Bibliometric Analysis of Educational Research Disseminated in Spanish Journals Between 1990 and 2002 - Ceferina Anta Cabreros (Universidad Autónoma de Baja California, 2008)
<span style="color: #000000; font-family: Arial, Helvetica, sans-serif; font-size: small; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; background-color: #ffffff; display: inline !important; float: none;">This article displays the data collected from the analysis of 3,118 documents on educational research between the years 1990 and 2002. The analysis was made through the paradigm of sociology of science, with the purpose of observing the social and organizational contexts where this knowledge area takes place, such contexts are explained through the following indicators: productivity rate, authorships and collaboration indexes, magazine titles according to the Bradford S. C. model and institutional affiliation of the authors. On the other hand, the content analysis method is applied with the aim of observing the levels and subject matters that have been reffered to in the articles. The results are presented in 8 categories and 28 variables.